A Conceptual Model of Service Quality and Its Implications for Future Research - Parasuraman, A.; Zeithaml, Valarie A.; Berry, Leonard L. (Journal of Marketing, 1985)
The attainment of quality in products and services has become a pivotal concern of the 1980s. While quality in tangible goods has been described and measured by marketers, quality in services is largely undefined and unresearched. The authors attempt to rectify this situation by reporting the insights obtained in an extensive exploratory investigation of quality in four service businesses and by developing a model of service quality. Propositions and recommendations to stimulate future research about service quality are offered.